Cellular pathways linked to dominant Parkinson’s disease - Lewis, Patrick A. (Henry Stewart Talks, 2014)
Three genes are linked to autosomal dominant Parkinson's: SNCA, LRRK2 and VPS35, Pathology and symptoms overlap with idiopathic disease, but display key differences, Multiple pathways disrupted, with recent data supporting alterations in lysosomal function